Comparison of sagittal lumbosacral parameters in patients with ankylosing spondylitis and chronic mechanical back pain (Annals of Medical Research, 2021)
None
Keywords: Ankylosing Spondylitis; Lumbosacral Balance; Lumbosacral Alignment; Lumbar Lordosis; Inflammation.